Sulfanilic acid-modified chitosan mini-spheres and their application for lysozyme purification from egg white - Hirsch, Daniela Belén (2018)
A cation exchange matrix with zwitterionic and multimodal properties was synthesized by a simple reaction sequence coupling sulfanilic acid to a chitosan based support. The novel chromatographic matrix was physico-chemically characterized by ss-NMR and ζ potential, and its chromatographic performance was evaluated for lysozyme purification from diluted egg white. The maximum adsorption capacity, calculated according to Langmuir adsorption isotherm, was 50.07 ± 1.47 mg g-1 while the dissociation constant was 0.074 ± 0.012 mg mL-1 . The process for lysozyme purification from egg white was optimized, with 81.9% yield and a purity degree of 86.5%, according to RP-HPLC analysis. This work shows novel possible applications of chitosan based materials. The simple synthesis reactions combined with the simple mode of use of the chitosan matrix represents a novel method to purify proteins from raw starting materials.